Usos do passado: Gália, Hispânia e suas relações; Júlio César e Asterix, o gaulês - Simonaio, Arthur De Moraes (2016)
We want to analyze how Julius Caesar builds the Gauls and Romans in the image Commentarii Bello Gallico and its appropriations in the comics of Asterix and Obelix. Search is will establish a research analysis understanding the formation of the figure of leaders, Julius Caesar and Vercingetorix, in the studied sources. The analysis to be undertaken will include the war in Hispania and Gaul and its consequences in Roman politics. The Gauls later had their appropriate images in France and a reflection of these representations were the comic book Asterix and Obelix, which are part of this thesis proposes to analyze the historical buildings that incorporate the Hq`s, particularly in the journal "Asterix in Hispania." The construction of the image of Gaul and the Gauls and its relationship with the Romans, even if through the eyes of Caesar, integrate this analysis.